(3GdehGgH GddOfjI aj GdefM GdeMeOjIs - (3CMeO Hf eMeO Hf CHj HcQ Hf YHO Gdedc GdbJjHj GdeUQj GdbSWdGfj , TgGH GdOjf CHh GdYHGS,J (B923 (3g` s ((3eMeO GdaVdi GdYeQi s)
(3ChdgG (B:s
(3GdebUO GdNGeS ai JNUjUI Ydjg GdUdGI hGdSdGe HNUGFU GdeYQGL hGdESQGA s
(3BNQgG (B:s
(3bGd eDdag hLGeYg agPG eG LQi iHg bde GdeOO ef gPg Gd ehGgH hSWQJg jO GdajV ef GdefM GdeMeOjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMI hebGHdI heVHhWg Ydi YOI fSN hYdi TQM GdRQbGfi SfI (B1191 (3g` Ws
(3cJHJ HYV GdcdeGJ HGdMeQI s
(3, ebSe KdGKI YdH ecQhajdejI fXQkG dcHQ MLeg C , H, L s
(3bQf GdfSN (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs